Organizing and Managing for Excellence and Equity: The Work and Dilemmas of Instructionally Focused Education Systems. Issue 6 (September 2019) - Peurach, Donald J.; Yurkofsky, Maxwell M.; Sutherland, Daniella Hall
A sustained policy press to improve quality and reduce disparities in public education is driving U.S. public school districts to organize and manage instruction for excellence and equity. The purpose of this analysis is to elaborate and to animate patterns and dilemmas in this work. The analysis identifies five domains of work central to this transformation, four patterns in the distribution of this work among central offices and schools, and four dilemmas endemic to the work. It then uses the preceding to frame vignettes of that work and those dilemmas as playing out in four different public school districts.